SEM/EDX analysis of stomach contents of a sea slug snacking on a polluted seafloor reveal microplastics as a component of its diet - Giulia Furfaro; Marcella D’Elia; Stefania Mariano; Egidio Trainito; Michele Solca; Stefano Piraino; Genuario Belmonte (Scientific Reports, 2022)
Abstract Understanding the impacts of microplastics on living organisms in aquatic habitats is one of the hottest research topics worldwide. Despite increased attention, investigating microplastics in underwater environments remains a problematic task, due to the ubiquitous occurrence of microplastic, its multiple modes of interactions with the biota, and to the diversity of the synthetic organic polymers composing microplastics in the field. Several studies on microplastics focused on marine invertebrates, but to date, the benthic sea slugs (Mollusca, Gastropoda, Heterobranchia) were not yet investigated. Sea slugs are known to live on the organisms on which they feed on or to snack while gliding over the sea floor, but also as users of exogenous molecules or materials not only for nutrition. Therefore, they may represent a potential biological model to explore new modes of transformation and/or management of plastic, so far considered to be a non-biodegradable polymer. In this study we analysed the stomachal content of Bursatella leachii, an aplysiid heterobranch living in the Mar Piccolo, a highly polluted coastal basin near Taranto, in the northern part of the Ionian Sea. Microplastics were found in the stomachs of all the six sampled specimens, and SEM/EDX analyses were carried out to characterize the plastic debris. The SEM images and EDX spectra gathered here should be regarded as a baseline reference database for future investigations on marine Heterobranchia and their interactions with microplastics.